2020
DOI: 10.3390/genes11101131
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of microRNAs in Chlorella sorokiniana Using High-Throughput Sequencing

Abstract: Chlorella is a popular microalga with robust physiological and biochemical characteristics, which can be cultured under various conditions. The exploration of the small RNA content of Chlorella could improve strategies for the enhancement of metabolite production from this microalga. In this study, stress was introduced to the Chlorella sorokiniana culture to produce high-value metabolites such as carotenoids and phenolic content. The small RNA transcriptome of C. sorokiniana was sequenced, focusing on microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…miRNAs can regulate gene expression through destabilization of the mRNA and translational repression ( Chung et al, 2017 ). Most miRNAs are involved in regulating the biosynthesis of secondary metabolites, followed by protein metabolism ( Azaman et al, 2020 ). From the above results, it can be seen that the transcription level of genes related to amino acid synthesis in C. pyrenoidesa is regulated by miRNAs, and miRNAs have a certain influence on nitrogen entering C. pyrenoidesa to synthesize amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs can regulate gene expression through destabilization of the mRNA and translational repression ( Chung et al, 2017 ). Most miRNAs are involved in regulating the biosynthesis of secondary metabolites, followed by protein metabolism ( Azaman et al, 2020 ). From the above results, it can be seen that the transcription level of genes related to amino acid synthesis in C. pyrenoidesa is regulated by miRNAs, and miRNAs have a certain influence on nitrogen entering C. pyrenoidesa to synthesize amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are key regulators in gene expression that can control gene expression via messenger RNA (mRNA) cleavage or translational repression ( Djami-Tchatchou et al, 2017 ; Lou et al, 2018 ). Meanwhile, miRNA-target genes are primarily involved in secondary metabolite biosynthesis ( Azaman et al, 2020 ). Microalgae nitrogen metabolism can be influenced by both miRNA and mRNA, and the presence of yeast stimulates gene expression in microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the investigation of algae miRNAs has gained more attention due to their vital function in metabolic processes and adaptation to various stresses. Currently, different algae miRNAs genes, including Chlamydomonas reinhardtii [ 43 , 44 , 45 ], Chlorella sorokiniana [ 46 ], and Botryococcus braunii [ 47 ], have been identified, and some of them also have been well characterized. However, the role of miRNAs in lipid accumulation under nitrogen deprivation stress for microalgae is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies focused on microalga miRNAs and their potential functions. Azaman et al identified miRNAs from Chlorellasorokiniana , and 98 miRNAs were identified in cultured microalgae subjected to normal and stress conditions (Azaman et al, 2020). Deng et al found that miRNAs inBotryococus braunii were involved in metabolic and cellular processes, gene expression regulation, and stress/defense functions (Deng et al 2017).…”
Section: Food-derived Mirnas Abundant In Serum Exosome Of Pearl Oyste...mentioning
confidence: 99%